Gaza's new Islamists: The atomization of Palestinian Islamism since 2006 - Leila Stockmarr (Danish Institute for International Studies (DIIS), 2011)
The emergence of new Islamist groups challenging Hamas from within is demarcating a new tendency towards inter-Islamist rivalry in Gaza. Based on original empirical data this report maps the Islamist milieu in Gaza. It offers a critical examination of how Hamas has governed Gaza since 2007 and why new Islamist groups in Gaza have emerged. The report argues that the phenomenon of new Islamists is diffuse and intangible. It does, however, relate to the question of the ideological price of governing in Palestine, and the repercussions of Hamas' rule and external policies upon the Islamist milieu in Gaza where, for the first time, an Islamist political body is in power. Two major aspects are motivating the emergence of new Islamist agendas: people's ideological grievances towards those in power and the instrumentalisation of ideology and religion in the midst of a power struggle between an increasingly authoritarian political body and its dissidents and challengers. In the face of governments which are failing to deliver, non-organised religious activity has become political power in Gaza.
Keywords: 300